Strategies to Mitigate the Negative Impact of Social Media on Religious Understanding in the Digital Era - Asmarita Lutfita Dewi; Vini Shulistiawati; Zuliyantika Rizmandani (al-Afkar, Journal For Islamic Studies, 2026)
This research examines the negative impact of social media on religious understanding in the digital era and explores mitigation strategies that can be implemented. The objective of this study is to identify the forms of distorted religious understanding that arise from social media, analyze public responses to online religious narratives, and formulate mitigation strategies based on various social actors. This research uses a descriptive qualitative approach with data collected through literature review, participatory observation on social media platforms (YouTube, Instagram, TikTok, and Twitter), and semi-structured interviews with five informants consisting of religious figures, Islamic education teachers, and university students. The findings show that social media has become a dominant space for shaping religious understanding, yet often presents unverified and oversimplified content, leading to misinformation and symbolic radicalization. Public responses are polarized into two main tendencies: passive acceptance and critical selectivity, both influenced by the level of digital religious literacy. Mitigation strategies must involve individuals, religious communities, educational institutions, and the state, through systemic and collaborative approaches. In conclusion, mitigation efforts should not only reduce harmful content but also promote a reflective, tolerant digital culture rooted in moderate Islamic values. This study offers both conceptual and practical contributions to the effort of fostering a healthy digital religious sphere amidst the complexities of the information age.